Hematologic reference intervals for Xenopus tropicalis with partial use of automatic counting methods and reliability of long‐term stored samples. (3rd May 2016) - Maxham, Lily A.; Forzán, María J.; Hogan, Natacha S.; Vanderstichel, Raphaël V.; Gilroy, Cornelia V.
Abstract : Background: The African frog, Xenopus tropicalis, is widely used in biomedical and toxicologic research. Reference intervals (RI) for hematologic variables, valuable to research and health status assessment, have not been established. Objectives: The purpose of the study was to determine hematologic RI of X tropicalis, and establish whether automated cell counting can facilitate routine hematologic assessment in frogs. Methods: Blood from 41 adult healthy X tropicalis was collected via cardiac puncture, and diluted in Natt–Herrick solution. Complete WBC, RBC, and thrombocyte counts (hemocytometry), differential WBC counts (Wright–Giemsa‐stained smears), PCV (centrifugation), total protein (refractometry), and automated total cell counts (WBC + RBC + thrombocytes, Sysmex particle counting) were determined. Concordance correlation coefficients calculated the agreement between total cell counts obtained by hemocytometry and automated particle counting, and between total cell counts at collection and after 2 years of storage. Results: Leukocyte morphology was similar to other amphibians and mammals. PCV was similar to other frogs; RBC counts were higher, and MCV was lower than in other frog species. Neutrophils were the most numerous WBC. Agreement was good between hemocytometry and automated cell counts. Subtracting the hemocytometer WBC and thrombocyte counts from the automated total cell count reliably yielded the RBC count. Cellular integrity evaluated 2 years post collection was good, and automated counts were not clinically different from counts at collection. Conclusion: We provide hematologic RI for X tropicalis, suggest how automated cell counts may facilitate hematologic assessments of frogs, and establish that blood in Natt–Herrick solution is stable 2 years post collection.